Digitalisasi Industri Konstruksi dengan Integrasi BIM dan 3D Machine Control untuk Meningkatkan Performa Pelaksanaan Konstruksi - Iwan Hermawan; Sutardi Sudirman (Jurnal Teknik Sipil, 2023)
The Government of the Republic of Indonesia through Presidential Regulation Number 100 of 2014 and Presidential Regulation Number 117 of 2015 aims the construction of the 2770 km Trans Sumatra Toll Road from Bakauheni to Banda Aceh to be fully constructed by 2024. There are two key stages in the project phase, i.e planning and construction stages. The planning stage is carried out using the Building Information Model (BIM), while the construction phase integrates BIM with 3D-Machine-Control. This study is conducted in Trans Sumatera Pekanbaru - Bangkinangs Toll Road with 40 kilometers long as a study case. The data acquisition methodology is conducted using qualitative and quantitative methods throughout the fields experiments. This study conducted the examination of the LiDAR UAV digital surveys accuracy, the BIM implementation on Level of Development (LOD) 200, 300, and 400, verification of the usage of Motor Grader with 3D-Machine-Control efficiency in elevation cutting works, and the application of Vibro Compactor with 3D-Machine-Control for improving the accuracy of soil compaction on the subgrade and base course. The results showed that the topographic data from UAV LiDAR are accurate within LE90 accuracy with 0.176 cm. The optimalization of 3D-Machine-Control could carry out the earthworks as similar as design also can be used as quality and quantity control. The time efficiency which obtained from implementing Motor Grader with 3D-Machine-Control for elevation cutting application is 47 percent.